Criminal Liability of Child in Drug Circulation Case (Study of Decision Number 31/PID.SUS.ANAK/2015/PN.BKS)Criminal Liability of Child in Drug Circulation Case (Study of Decision Number 31/PID.SUS.ANAK/2015/PN.BKS) - Mutia Nursanti; Rahtami Susanti; Bayu Setiawan (UMPurwokerto Law Review, 2021)
The Indonesian Child Protection Commission (Komisi Perlindungan Anak Indonesia, KPAI) found an increase in the involvement of children in the narcotics trade. In 2018, 5.9 million children in Indonesia were exposed as narcotics addicts, 27 percent of them or 1.6 million became narcotics dealers. This study aims to determine the criminal responsibility of children in narcotics trafficking cases in Decision Number 31/Pid.Sus.anak/2015/PN.BKS. The method used in this research is normative juridical. Based on the results of the study, the criminal responsibility of children in narcotics trafficking cases was legally and convincingly proven guilty of violating Article 111 paragraph (1) in conjunction with Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics and sentenced to imprisonment for 7 months taking into account that the Defendant's actions are contrary to the government's program which is actively eradicating narcotics trafficking, the Defendant regrets his actions and promises not to do it again, the Defendant is still underage and lacks attention from his parents, the Defendant has never been punished. So that narcotics cases against children do not grow rapidly, an anti-narcotics ambassador program is held in each school regularly every year so that school students are always reminded not to abuse narcotics and in the RT/RW/Village community a task force for handling narcotics abuse is formed to prevent abuse as early as possible. narcotics in the environment are still. Keywords: Criminal Liability, Children, Narcotics Circulation